The Effect of Temperature Changes on in vitro Slow Wave Activity in the Equine Ileum. (9th September 2013) - Fintl, C.; Hudson, N.P.H.; Handel, I.; Pearson, G.T.
Abstract : Aims: To evaluate the effect of temperature changes on in vitro slow wave activity of the equine ileum using intracellular recording techniques. Methods: A section of ileum was collected immediately following euthanasia from 9 normal horses euthanased for clinical reasons unrelated to the gastrointestinal tract. Intestinal tissue samples were cut into 1 mm thick sections, pinned out on a Sylgard plate and superfused with warmed, oxygenated Krebs solution. Intracellular recordings of membrane potential were made from smooth muscle cells using glass microelectrodes. All experiments were performed in the presence of a calcium channel blocker to ensure stable impalements. The temperature of the tissue bath was altered during the course of the experiment at a range of 27–41°C. All data were recorded and stored using a computer interfaced acquisition system. A software package was used to analyse the resting potentials, the amplitude, frequency and duration of slow waves. Results: In all 9 horses slow wave frequency appeared to be approximately linearly related to the temperature over the range studied increasing by 0.5 cycles/min for each 1 degree increase in temperature (P<0.01). The initial slow wave frequency resumed when the temperature was returned to 37°C. The recovery time appeared to be directly related to the duration for which the temperature had been changed. Conclusions: Slow wave frequency in the equine ileum is highly temperature sensitive. Practical significance: As post operative ileus is a major cause of morbidity and mortality in the horse, the negative effect of lower temperatures on slow wave activity should be considered. During colic surgery close attention should be paid to minimising extra‐abdominal gut exposure time and keeping the temperature of the intestinal and abdominal lavage fluids at body temperature. Ethical animal research: Post mortem samples obtained with the consent of the owners.Sources of funding: The Norwegian Agricultural Agreement Research Fund, Norsk Rikstoto and the Research Council of Norway as part of the Norwegian/Swedish research collaboration.Competing interests: None.